The role of magnetic agents in shaping post-disaster land use - Zavar, Elyse (Land Use Policy, 2016)
Three neighborhoods in Lexington, Kentucky, share a common flood history, including property acquisitions, as a means to mitigate against flooding; yet, the interactions of residents with the buyout landscapes vary significantly among the neighborhoods. Although the same institutions and structural controls implemented flood buyout programs in all three neighborhoods, semi-structured interviews illustrate that differing perspectives, personalities, and neighborhood politics shaped unique identities and land uses for the acquired properties in each neighborhood. Varying levels of resident engagement with the buyout landscape resulted in a range of attitudes towards hazard preparation, management, and mitigation, thus leaving some neighborhoods more resilient to future flooding than others. This study explores key residents, termed magnetic agents, who drove neighborhood civic action and land uses on the open space created through floodplain property acquisition. This research indicates magnetic agents can serve as important partners for local governments and non-governmental organizations (NGOs) in building community-based projects aimed at reducing vulnerability to flood events and instituting high utility land uses on floodplain buyout open space.(C) 2016 Elsevier Ltd. All rights reserved.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-794-376-727-198 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Agency; Floodplain buyout; Kentucky; Land management; Lexington; Resiliency; United States; dept.egm; flooding; floodplain; hazard management; land management; land use planning; neighborhood; open space

Residential perspectives: the value of Floodplain‐ buyout open space - Zavar, Elyse (Geographical Review, 2015)
This mixed-methods case study identifies how floodplain property acquisitiona buyoutimpacts an urban environment at the neighborhood scale while considering the role of individual residents in formal and informal land-use decision making. In floodplain buyouts, the reopening of urban space is enabled by federal structural drivers, primarily Federal Emergency Management Agency (FEMA), but it is repurposed as a cultural landscape constructed and produced by individuals. This research explores how residents perceive and ascribe values to the buyout landscape in Lexington, Kentucky. Enabled by federal funds, but left largely to their own devices, residents in Lexington adopted uses, ascribed values, and produced their own land-use norms in each buyout neighborhood.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-849-610-654-018 tex.type: [object Object]
Keywords: dept.egm; floodplain; land management; land value; peer-reviewed; property acquisition

Understanding the role of wrongdoing in technological disasters: Utilizing ecofeminist philosophy to examine commemoration. - Roe, Sarah M.; Zavar, Elyse (Studies in history and philosophy of science, 2021)
Stemming from human accident, error, or neglect, technological disasters, such as chemical spills, toxic waste contamination, nuclear radiation, transportation accidents, and factory explosions, are products of the modern industrial complex. Toxic contamination of the land can permanently displace people from their homes and erase places from the landscape. Commemoration provides an opportunity to remember the past and celebrate culturally significant place attachments while contributing to the recovery process by aiding in community healing after devastating events. We focus on two key components regarding commemoration after technological disaster, namely the acknowledgement of wrongdoing and the celebration of a resilient population and landscape. We argue that a combination of ecofeminist philosophy and environmental justice frameworks allows for a better understanding of the cycle of disaster and mitigation as it pertains to targeted groups, and that commemorative acts and artifacts following human-made disasters often fail to successfully reform this cycle. Moreover, the combination of ecofeminist philosophy and environmental justice allows us to examine the complex relationship between responsibility and targeted groups through disaster commemoration, which serves as an important way to communicate wrongdoing to both the local and greater population. Through engagement with ecofeminist philosophy and environmental justice frameworks, we explicate how commemoration after technological disaster can disrupt or reinforce systematic inequalities. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31] http://www.ncbi.nlm.nih.gov/pubmed/34111819 ; https://europepmc.org/article/MED/34111819 ; https://philpapers.org/rec/ROEUTR ; https://www.ncbi.nlm.nih.gov/pubmed/34111819
Keywords: article; artifact; contamination; dept.his; disaster; explosion; factory; human; justice; neglect; peer-reviewed; philosophy; responsibility; toxic waste

Land use change on US floodplain buyout sites, 1990-2000 - Zavar, Elyse; Hagelman, III, Ronald R. (Disaster Prevention and Management, 2016)
Purpose - The Federal Emergency Management Agency provides guidelines for the management of open space created through property acquisition (buyouts); however, land use decisions are primarily left to local governments manifesting in a variety of uses. The purpose of this paper is to provide a land use assessment of buyout sites, to describe the changes in those uses that have occurred during a ten-year period from 1990 to 2000, and to offer an assessment of management approaches employed across these sites. Design/methodology/approach - Using a mixed-methods approach consisting of a land use classification survey and a semi-structured questionnaire of floodplain managers, this study explores the land use trends at buyout sites, diverse approaches local governments take in managing the open spaces created through floodplain buyout programs, and the successes and challenges communities face in open space management. Findings - Results indicate strong support from floodplain managers for property acquisition and several cases emerged where communities put their newly acquired public land to creative uses. However, the opportunity to leverage these properties for greater public values is largely being missed, primarily because of limited funding. Practical implications - The analysis indicates strong support among floodplain managers for the buyout approach; however, additional resource-sharing and funding opportunities are needed to increase the utility of buyout properties. Originality/value - By evaluating the long-term management strategies floodplain managers utilize on buyout sites, this study adds to an underrepresented area of scholarship and is of value to practitioners, government officials, and academics.
44 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-423-912-140-83X tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Buyout; Disaster mitigation; Floodplain management; Land use; dept.egm

Land-use change at temporary group-housing sites in post-Katrina Louisiana - Zavar, Elyse; Hagelman, III, Ronald; Lavy, Brendan; Prince, Benjamin (Natural Hazards Review, 2017)
To shelter the large number of displaced households following Hurricane Katrina (2005), FEMA, in conjunction with local governments, established 110 temporary group-housing sites throughout impacted Louisiana. The purpose of this study is to identify how temporary group-housing sites influenced the land use of post-Katrina Louisiana. Using aerial imagery, this study assessed the land use of each temporary group-housing site prior to Hurricane Katrina in 2005 and again in 2010. Of the 110 group-housing sites, 54.5% reverted to the previous land use, 29.1% returned to the previous land use with improvements, and 16.3% of the sites changed land use. Using census data from 2000 and 2010, site characteristics, and property records, this study employed a multinomial logistic regression to identify statistically significant variables in predicting land-use change in post-Katrina Louisiana. The results indicate that, especially in neighborhoods with high demand for land, FEMA temporary group-housing sites tended to be redeveloped into new land uses.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/146-296-911-884-194 tex.article-number: [object Object] tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Aerial imagery; Aerial photography; Group housing; Housing; Hurricane Katrina; Hurricane Katrina 2005; Hurricane katrina; Hurricanes; Land use; Land-use change; Local government; Louisiana; Multinomial logistic regression; Population statistics; Significant variables; Site characteristics; Temporary group housing; United States; aerial photograph; census; dept.egm; hazard assessment; hazard management; housing project; land use change; local government; neighborhood